PERFORMA SAHAM OPERATOR SELULER DI LQ45: ANALISIS EXPECTED RETURN DAN STANDAR DEVIASI PADA SAHAM TLKM, EXCL, DAN ISAT - Jevan Michael; Shella Koirun Nisa; Serina Muslimah; Jazilatul Wafiroh (Draf Solusi Indonesia, 2025)
This study aims to analyze the performance of LQ45 mobile telecommunications stocks, specifically PT Telkom Indonesia Tbk. (TLKM), PT XL Axiata Tbk. (EXCL), and PT Indosat Tbk. (ISAT), over a 5-year period through expected return and standard deviation analysis. The evaluation is based on historical stock data to assess the risk and return profile of each company. TLKM, with a sum of expected return of 2,59% and an average of 0,002%, shows a relatively low standard deviation of 0,0187, indicating lower volatility. EXCL’s sum of expected return is 4,74%, with an average of 0,004% and a standard deviation of 0,0266, suggesting moderate risk. In contrast, ISAT exhibits the highest sum of expected return at 182,73%, with an average of 0,15%, but also the highest standard deviation at 0,0321, indicating greater volatility and potential reward. The findings reveal distinct risk-return profiles for each stock, with ISAT offering higher potential returns at the cost of increased volatility, while TLKM and EXCL present more stable, yet lower, return expectations. This analysis provides valuable insights for investors seeking to balance risk and return in the telecommunications sector within LQ45.